Enhancing microstructural and optoelectronic properties of CZTS thin films by post deposition ionic treatment - Azmi N.; Chelvanathan P.; Yusoff Y.; Ferdaous M.T.; Zuhdi A.W.M.; Tiong S.K.; Amin N. (Elsevier B.V., 2023)
Carrier concentration; Chlorine compounds; Copper compounds; Crystallinity; Magnetron sputtering; Sodium compounds; Thin films; Zinc compounds; CZTS thin films; Micro-structural; Optoelectronic properties; Orders of magnitude; Post-deposition; rf-Magnetron sputtering; Sulphurization; Urbach energy; Tin compounds